Food Ordering System Mobile Application - Lau, Shyh Shiuan Klinsman; Ibrahim, Rosziati (Applied Information Technology And Computer Science, 2022)
Food Ordering System is a mobile application developed for a café to help taking care of the customers’ calorie intake of their meals. The main objectives are to solve the existing problems of having long queue and to implement healthier meal for the customers, which may help in getting their business process smoother. I have chosen Android Studio as my integrated development environment (IDE) and Google Firebase as my database storage. Java language will be used as the main programming language to implement object-oriented programming method. This project is done during the COVID-19 pandemic and therefore, there are some Standard Operating Procedure (SOP) to be followed by the café. This mobile application may provide some assistance in helping them to increase their business performance during this pandemic.